Dynamics of Nature-Based Learning in Developing Children’s Motoricic Skills: Teacher and Parent Perspectives - Lubis, Mukhlis; Saidah Yustika (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
A child's development, particularly in terms of motoric skills, is most formative during the first few years of life. One approach that is considered effective in optimizing children's motoric development is nature-based learning, which utilizes the natural environment as the main learning medium. This study aims to explore the dynamics of nature-based learning in developing early childhood motoric skills through literature studies. Articles, books, and scientific documents produced between 2015 and 2024 are reviewed in a literature review using a qualitative descriptive methodology.This study found that children's fine and gross motoric skills, as well as their social and emotional development, can benefit from learning in natural settings. However, its implementation in Indonesia still faces challenges, especially related to parents' perceptions of child safety and the limitations of teachers' creativity in designing outdoor activities. This study provides active support from parents and increasing teacher capacity as an effort to optimize nature-based learning in early childhood education.